Regional variation in directed swimming by Atlantic salmon smolts leaving Scottish waters for their oceanic feeding grounds—a modelling study. (5th October 2019) - Ounsley, James P; Gallego, Alejandro; Morris, David J; Armstrong, John D
Abstract: An understanding of the migratory trajectories and behaviours of Atlantic salmon post-smolts during the early marine phase of their life cycle is needed for effective conservation and marine planning. A simulation study of post-smolt migration from Scottish shores was carried out, combining a high-resolution hydrodynamic model of the Scottish continental shelf with a Lagrangian particle tracking model. Various different notional swimming behavioural scenarios were simulated, including current-orientated and compass-directed movement across a range of swimming speeds. Current-following behaviours did not facilitate migration towards feeding grounds in the North Atlantic. In addition, modelled trajectories resulting from directed-swimming behaviours imply that populations around Scotland need to adopt different locally adapted migratory strategies to successfully reach their feeding grounds.